2014
DOI: 10.1016/j.anbehav.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Tenure in current captive setting and age predict personality changes in adult pigtailed macaques

Abstract: Personality change in nonhuman primates is a topic that warrants more research attention. Many studies focus on intraindividual repeatability, but few note population-wide trends in personality change. In part, this results from the large sample size that is required to detect such trends. In the present study, we measured personality in a large sample (N = 293) of adult, mother-reared pigtailed macaques, Macaca nemestrinam, over a period of 3 years. We looked at four personality components (sociability toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Migration is typically accompanied by increases in mortality or injury rates, decreases in access to resources, and social costs, i.e., the loss of social ties or rank (Dittus 1979;Weiß et al 2016). Following migration, male rhesus macaques show more fearful and less physically aggressive behavior than before (von Borell et al 2016), which is consistent with findings from captive pigtailed macaques, where individuals that are new to a facility are more cautious (Sussman et al 2014). Migration may also trigger rank-order changes in behavior, possibly reflecting different reactions or strategies following migration.…”
Section: Stressful Life Experiencessupporting
confidence: 71%
“…Migration is typically accompanied by increases in mortality or injury rates, decreases in access to resources, and social costs, i.e., the loss of social ties or rank (Dittus 1979;Weiß et al 2016). Following migration, male rhesus macaques show more fearful and less physically aggressive behavior than before (von Borell et al 2016), which is consistent with findings from captive pigtailed macaques, where individuals that are new to a facility are more cautious (Sussman et al 2014). Migration may also trigger rank-order changes in behavior, possibly reflecting different reactions or strategies following migration.…”
Section: Stressful Life Experiencessupporting
confidence: 71%
“…Our results show that dominance rank is a major driver of several dimensions of personality, especially boldness and social approachability, although some intra-individual stability of boldness and anxiousness is detectable across groups and ranks. After controlling for rank, we also found that age predicted behavioral tendency, which may reflect overall age-associated declines in activity level (Moscrip et al, 2000) or more specific behavioral fluctuations that have been reported to occur with age in pigtail macaques ( Macaca nemestrina ) (Sussman et al, 2014). Together, these findings suggest that some behavioral tendencies in female rhesus macaques are more stable and trait-like (e.g.…”
Section: Discussionmentioning
confidence: 56%
“…These findings came from studies in settings as diverse as zoos and sanctuaries, laboratories and the field, and in studies that used ratings to assess personality [58][59][60][61][62][63][64][65] and studies that used behavioural observations and tests [66][67][68][69]. In addition, one of these studies [58] found that among female rhesus monkeys who gave birth for the first time between assessments, there were marked declines in the stabilities of the confident and sociable domains, but not for the excitable domain.…”
Section: (B) Stabilitymentioning
confidence: 99%
“…[77]) and behavioural tests and observations (e.g. [68]). However, it appears that only two studies tested whether the rate of personality change in primates matches the rate found in humans.…”
Section: (B) Personality and Ageingmentioning
confidence: 99%